(3GdNjd hGdaQhSjIs - (3CHh YHO Gddg fGUQ GdOjf , GHf GNj MRGe GdNWdj, CHh YHO Gddg fGUQ GdOjf , GHf GNj MRGe GdNWd,J (B250 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hdj GdMeO hCgdg CeG HYO aEfj de GRd HYOeG hgH Gddg dj ef eYQaI CdGJ GdaQhSjI eG hUaJg aj cJGHj gPG eeG jMJGL Gdjg Cgd GdLgGO aj SHjd Gddg s
(3BNQgG (B:s
(3djLF GdWHWGH eSJhjG eY GdGQV aEf de jJgjG dc Pdc ddYLGdI hGdeRGMeI dbQHgG dJQJaY ef GdGQV s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B145s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3GjGUhajG (B(2899) s
Keywords: (3eJaQbGJs